Controle estrutural na morfogênese de inselbergs em Quixadá- CE - Souza, Anna Sabrina Vidal de (2023)
Numerous inselbergs rise above the regional erosional surface in semiarid northeastern Brazil. The inselbergs are underlain by granites of Quixadá Pluton and are cut by dike swarms of different orientations, thicknesses, and compositions. Five inselbergs with abundant dikes from two different parts of the pluton were selected to investigate the role of dike patterns and morphological features of hillslopes on the evolution of residual granite topography. The methods included field mapping of landforms, structural measurements of accessible dike arrays, and rock strength determinations using a Schmidt hammer. Unmanned Aerial Vehicle (UAV) photogrammetry was used to build detailed digital terrain models of inselbergs and to recognize geometric patterns of dike arrays. In addition, more than 30 rock samples were collected to determine rock composition and evaluate their resistance to weathering. The results indicate that dikes exert clear but variable control on the morphology of granite inselbergs. The dip of the dikes is of main significance. Low-angle, sub-horizontal dikes increase rock-mass resistance, providing effective barriers for the descending weathering front, and are associated with the most prominent, steep-sided residual hills. By contrast, steeply-dipping dikes promote weathering and are hypothesized to underlie the plains between the inselbergs. At a small scale, dikes control the occurrence and evolution of minor rock landforms such as weathering pans, solution runnels, overhangs, and split boulders.